2018
DOI: 10.1002/app.46504
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasmall Ag nanocrystals supported on chitosan/PVA nanofiber mats with bifunctional properties

Abstract: Bifunctional nanofiber mats consisting of chitosan (CS), poly(vinyl alcohol) (PVA), and silver nanocrystals (Ag NCs) have been fabricated by a facile electrospinning method. The formation and presence of Ag NCs supported on CS/PVA nanofibers are confirmed by ultraviolet‐visible spectroscopy and X‐ray diffraction. The morphology of the samples is characterized by transmission electron microscopy and scanning electron microscopy. The prepared Ag NCs/CS/PVA nanofiber mats show pronounced antibacterial activity ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Chitosan (CS) is a natural base material with useful properties and poly(vinyl alcohol) (PVA) is also a type of nontoxic, water‐soluble, and biocompatible synthetic polymer that is commonly used as a mixture with CS developed through chemical linking . Generally, CS and PVA nanofibrous scaffolds are cross‐linked by glutaraldehyde (GTA) to elevate the mechanical properties of the fabricated nanofibrous composite scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan (CS) is a natural base material with useful properties and poly(vinyl alcohol) (PVA) is also a type of nontoxic, water‐soluble, and biocompatible synthetic polymer that is commonly used as a mixture with CS developed through chemical linking . Generally, CS and PVA nanofibrous scaffolds are cross‐linked by glutaraldehyde (GTA) to elevate the mechanical properties of the fabricated nanofibrous composite scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…To solve the problem, various modication techniques such as blending, graing, and crosslinking are employed. Among them, doping inorganic nanomaterials have become an important research direction, polymer nanocomposites membranes were prepared by PVA with nano-SiO 2 , 17,18 NaA zeolite, 19 nano-TiO 2 , 20 carbon nitride, 21,22 Ag, 23,24 and other inorganic nanomaterials. Arif et al 17 synthesized PVA/silica membranes by sol-gel derived route for application in pervaporation of isopropanol-water mixture.…”
Section: Introductionmentioning
confidence: 99%
“…All of the AgNCs/CS/PVA nanofiber mats had outstanding antibacterial activity, because AgNCs are lethal to bacteria. Filtration results showed that with the filtration time increasing to 600 min, the color of the nanofiber mats gradually became tan in color (insets), and the suspended particulate matter (SPM) filtration efficiency was still greater than 98%, which was much more efficient than ordinary commercial dust masks (76%) [ 57 ]. Zhang et al in an investigation synthesized A novel N -halamine biopolymer, P(ADMH-NVF), via a free-radical copolymerization of N -vinylformamide (NVF) and 3-allyl-5,5-dimethylhydantoin (ADMH), and combined with polyvinyl alcohol (PVA) as a middle layer [PVA/P(ADMH-NVF)].…”
Section: Introductionmentioning
confidence: 99%